Anthelmintic resistance and homeostatic plasticity (Brugia malayi) - Sudhanva S. Kashyap (Nature Portfolio, 2021)
Abstract Homeostatic plasticity refers to the capacity of excitable cells to regulate their activity to make compensatory adjustments to long-lasting stimulation. It is found across the spectrum of vertebrate and invertebrate species and is driven by changes in cytosolic calcium; it has not been explored in parasitic nematodes when treated with therapeutic drugs. Here we have studied the adaptation of Brugia malayi to exposure to the anthelmintic, levamisole that activates muscle AChR ion-channels. We found three phases of the Brugia malayi motility responses as they adapted to levamisole: an initial spastic paralysis; a flaccid paralysis that follows; and finally, a recovery of motility with loss of sensitivity to levamisole at 4 h. Motility, calcium-imaging, patch-clamp and molecular experiments showed the muscle AChRs are dynamic with mechanisms that adjust their subtype composition and sensitivity to levamisole. This homeostatic plasticity allows the parasite to adapt resisting the anthelmintic.